The Effect of Gamification in Loyalty Programs on the Loyalty of Marketplace User Using the Expectation-Confirmation Model (ECM) - Zunan Setiawan; Chevy Herli Sumerli A; Errie Margery; NYI Dewi Puspitasari; Alim Hardiansyah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study aims to determine the effect of user experience using gamification in loyalty programs on user loyalty. The number of samples in this study was 213 respondents who were marketplace users. Sampling was carried out using the purposive sampling technique. The data analysis process was carried out based on the PLS-SEM approach with SmartPLS version 3.2.8 software. The model used is a modified result of the Expectation-Confirmation Model (ECM). Overall, this study found that users feel satisfied and loyal to marketplace. Another result obtained is that 1 of 14 hypotheses is rejected. Based on the 13 accepted hypotheses, it can be concluded that the entertainment, trendy, intimacy, and novelty variables of the user experience using gamification have an influence on user loyalty through the hedonic value and utilitarian value variables.